Nutritive sweetener profiles of dairy-based beverages commercially available in Kota Bharu, Kelantan - Ramli, Roszamilahwati (Universiti Sains Malaysia, 2015)
Enzymatic technique was an alternative method applied in the sugar analysis of dairy-based beverages locally available in Malaysia. The technique was simple, using non-toxic chemicals, react rapidly, highly specific, and also sensitive to low concentration. The technique used to analyze several types of common sugars such as glucose, fructose, sucrose, lactose, and maltose. The measurement of the sugar concentration has been observed using the UV-Vis Spectrophotometry (Varian Cary 100) at 340nm wavelength. Based on the analysis which has been conducted, the dairy-based beverages majorly contained the sucrose and lactose sugar about 50% and 42% from the overall sugar. However, the amount of the total sugar does not in high level, therefore an individual can take other food or drinks to consume and control their sugar intake daily in order to prevent from exceeding the amount recommended by WHO.